PERSEPSI TAMU TERHADAP PROSES CHECK-IN OLEH RESEPSIONIS MELALUI OTA DI DJAKARTA HOTEL PADANG - Musparni - (Jurnal Public Administration, Business and Rural Development Planning, 2022)
The rapid growth of the hotel business has resulted in a very high level of competition between these hotels. For this reason, hotel managers must try their best to run and take advantage of the existing market by providing a good image and special services to their guests. In the era of globalization, the world of technology and information is developing very rapidly, one of which supports technology is the internet, which is an unlimited global online network that provides millions of types of information. So that many hotels use internet facilities in the room reservation process. This is because this method is considered to have several other advantages compared to a direct room reservation system, which will affect the behavior of the hotel both in terms of management and ordering and information services provided. Online media is one of the promotional tools that really helps the development of a hotel, in line with the development of technology, hotel room reservations are carried out by various methods: the reservation method is the method used by prospective guests to make room reservations, including telephone, letter, fax, hotel website, walk in and online travel agency. This type of travel agent provides online reservation services. Which later at check-in, guests will get a room voucher given by the OTA. Based on the findings in the field when carrying out observations or observations at the Front Office, there are several things that have not been maximized in carrying out the duties of this department. So it was found in the field that there were differences in views in the check-in process carried out by the receptionist against guests who came through the Online Travel Agent (OTA) in terms of the receptionist who did not ask for the voucher brought by the Online Travel Agent (OTA) guest so that receptionist officers do not carry out appropriate procedures in receiving guests through Online Travel Agents, so that when guests check-in, there are several guest complaints about front office services, especially in showing the identity of a legal husband and wife to the receptionist. Also at check-in, guests feel uncomfortable when showing the identity of the couple. Sometimes the clerk also forgets to ask for the room booking voucher that has been given by Traveloka and causes guests to be unhappy, which should be a very important thing in order to avoid mistakes when registering guests who will stay.